Cholesterol efflux analyses using stable isotopes and mass spectrometry - Brown, Robert J. (2012)
Cholesterol efflux from macrophages and the vascular wall is the initial step of the cardiovascular protective reverse cholesterol transport process. This study demonstrates a mass spectrometry based assay to measure the cellular and media content of [d(7)]-cholesterol and unlabeled cholesterol that can be used to measure cholesterol efflux from cell lines. Using a triple quadrupole ESI-MS instrument in direct infusion mode, product ion scanning for m/z 83, neutral loss (NL) 375.5 scanning and NL 368.5 scanning were used to detect cholesterol (as an acetylated derivative), [d(7)]-cholesteryl ester (CE) and unlabeled CE, respectively. The same mass of [d(7)]-cholesterol was substituted for [(3)H]-cholesterol under standard efflux assay conditions. At the end of [d(7)]-cholesterol loading, the intracellular mass of [d(7)]-cholesterol was 2-fold greater than unlabeled cholesterol, and the intracellular [d(7)]-CE profile is similar to unlabeled CE. Efflux of cholesterol to apolipoprotein A-I and high-density lipoproteins was similar when comparing efflux of either [d(7)]-cholesterol or [(3)H]-cholesterol as measured by following efflux of the tracers only. This technique also can be used to assess the efflux of unlabeled cholesterol to acceptors in media that are initially cholesterol-free (e.g., apolipoprotein A-I). Taken together, this mass spectrometry based assay provides new molecular detail to assess cholesterol efflux.